Al-Ghazali's Concept of Tazkiyatun Nafs as a Method in Moral Education - Muhammad Hafidz Khusnadin; Muhammad Fahmi Shihab (Oasis : Jurnal Ilmiah Kajian Islam, 2025)
This research aims to examine the implementation of Al-Ghazali's concept of tazkiyatun nafs as a method in moral education. The method in this research is descriptive qualitative method in which the author collects data by literature study (literature review) from various sources such as books, articles, and the internet related to the research theme. The results of this study indicate that the concept of tazkiyatun nafs Al-Ghazali can be implemented as moral education because it basically leads to the process of purifying the soul by eliminating various despicable traits, accustoming praiseworthy behavior and getting closer to Allah. With these stages, it can form the personality of students who are more noble. The conclusion of this research is that the concept of tazkiyatun nafs if implemented in the field of education can be a method of moral education can be done by strengthening the role of the teacher as a teacher of the concept of tazkiyatun nafs and a role model for students, integrating the concept of tazkiyatun nafs as part of the school education curriculum in various subjects, and adopting a learning model that is able to support students through the stages of takhali, tahalli, and tajali in order to form students who have intellectual, moral and spiritual intelligence. It is expected for teachers and schools to be able to support character and moral education programs among students based on the concept of tazkiyatun nafs Al-Ghazali.